Iron-based alloy composite wear-resistant material for preparing roller sleeve flux-cored wire
By adding nano yttrium oxide and modified carbon fibers to the iron-based alloy, the problem of increasing brittleness in traditional iron-based alloys when improving wear resistance is solved, and higher hardness, toughness and wear resistance are achieved.
Patent Information
- Application Number
- CN202411887428.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-20
AI Technical Summary
When improving wear resistance, traditional high-carbon and high-ferrochromium-based alloys need to add a large amount of hard phases, resulting in increased brittleness and falling off of the hard phase affects wear resistance.
The iron-based alloy composite wear-resistant material is used, and the rare earth element nano yttrium oxide and modified carbon fiber are added. By refining the primary carbides of the alloy and changing the microstructure structure, the hardness and wear resistance of the surfacing layer are improved.
The hardness, toughness and wear resistance of iron-based alloy composite wear-resistant materials are significantly improved, the wear amount is reduced, and the tendency to brittleness is avoided.
Smart Images

Figure BDA0005199718330000151 
Figure BDA0005199718330000161
Abstract
Description
Technical Field
[0001] The present application relates to the field of surfacing material technology, and in particular to an iron-based alloy composite wear-resistant material for preparing roller sleeve cored wire. Background Art
[0002] In modern industrial production, roller presses are a key processing equipment widely used in many fields such as metallurgy, mining, building materials, and chemicals. The main working parts of a roller press are one or more pairs of roller sleeves that cooperate with each other, which squeeze, grind, or crush the material under high pressure to achieve the desired processing effect. Since the roller sleeves are in direct contact with the processed materials, they are subject to tremendous pressure and wear during operation, especially when processing materials with high hardness and strong abrasiveness. The wear problem of roller sleeves is particularly prominent. In order to extend the service life of the roller sleeves and maintain their efficient working performance, surfacing technology has become an important means of roller sleeve maintenance and repair. Surfacing is the process of adding a layer of wear-resistant material to the surface of the roller sleeve. This layer of material usually has higher hardness and wear resistance than the original roller sleeve material, and can resist wear and impact, thereby protecting the roller sleeve body from damage. Surfacing technology can not only restore the original size of the roller sleeve, but also improve its wear resistance and corrosion resistance, reducing downtime and maintenance costs caused by wear.
[0003] In the field of cladding, flux-cored wire is a highly efficient welding material that is widely used due to its superior performance and ease of operation. Flux-cored wire can be divided into iron-based, nickel-based, cobalt-based, etc. according to the alloy composition. Iron-based wear-resistant cladding materials are widely used in the industrial field due to their low price and good performance.
[0004] However, in order to improve the wear resistance of traditional high-carbon, high-chromium iron-based alloys, a large amount of hard phases often need to be added, but this will increase the brittleness of the alloy, causing the hard phase to fall off and affecting the wear resistance. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present application provides an iron-based alloy composite wear-resistant material for preparing roller sleeve cored wire.
[0006] The present application provides an iron-based alloy composite wear-resistant material for preparing a roller sleeve cored wire, which adopts the following technical solution:
[0007] The invention discloses an iron-based alloy composite wear-resistant material for preparing a roller sleeve cored wire. The raw materials include, by mass percentage, 52-58% high carbon ferrochrome, 1-3% chromium nitride, 1-2% graphite, 8-11% aluminum powder, 0.8-1.5% nano yttrium oxide, 1-2% modified carbon fiber, and the balance is reduced iron powder; the modified carbon fiber is a cerium oxide / reduced graphene oxide composite material modified carbon fiber.
[0008] Preferably, the raw materials include 53-57% high carbon ferrochrome, 1.5-2.5% chromium nitride, 1.3-1.7% graphite, 9-10% aluminum powder, 0.9-1.4% nano yttrium oxide, 1.3-1.7% modified carbon fiber, and the remainder is reduced iron powder.
[0009] Preferably, the raw materials include 55% high carbon ferrochrome, 2% chromium nitride, 1.5% graphite, 9.5% aluminum powder, 1.15% nano yttrium oxide, 1.5% modified carbon fiber, and the remainder is reduced iron powder in percentage by mass.
[0010] Preferably, the modified carbon fiber is prepared from the following raw materials in parts by weight: 0.1-0.3 parts of carbon fiber, 1-3 parts of pretreated cerium oxide / reduced graphene oxide composite material, 40-80 parts of anhydrous ethanol, and 15-30 parts of silane coupling agent.
[0011] Preferably, the carbon fibers are short fibers.
[0012] Preferably, the pretreated cerium oxide / reduced graphene oxide composite material is prepared from the following raw materials in parts by weight: 1-5 parts of cerium oxide / reduced graphene oxide composite material, 20-100 parts of anhydrous ethanol, and 6-30 parts of silane coupling agent.
[0013] Preferably, the silane coupling agent is KH-560
[0014] Preferably, the cerium oxide / reduced graphene oxide composite material is prepared from the following raw materials in parts by weight: 0.6-1.2 parts of graphene oxide, 300-600 parts of water, and 4.2-9.6 parts of cerium nitrate hexahydrate.
[0015] Preferably, the mass ratio of the graphene oxide to the cerium nitrate hexahydrate is 1:7-8.
[0016] Preferably, the mass ratio of the graphene oxide to the cerium nitrate hexahydrate is 1:7.58.
[0017] Preferably, the method for preparing the cerium oxide / reduced graphene oxide composite material comprises the following steps:
[0018] Graphene oxide is added to water, ultrasonically dispersed, cerium nitrate hexahydrate is added, stirred for 3-5 hours, and allowed to stand for 24-30 hours. The obtained mixture is transferred to a polytetrafluoroethylene-lined high-pressure reactor and reacted at 160-200°C for 12-15 hours. After the reaction is completed, it is cooled, washed with deionized water, filtered to neutrality, and freeze-dried for 6-10 hours to obtain a cerium oxide / reduced graphene oxide composite material.
[0019] Preferably, the method for preparing the modified carbon fiber comprises the following steps:
[0020] The carbon fiber is added to anhydrous ethanol, ultrasonically dispersed for 1-2 hours, and then a silane coupling agent is added, stirred at 60-70° C. for 6-10 hours, and then the pretreated cerium oxide / reduced graphene oxide composite material is added, and stirring is continued for 6-10 hours. After washing and drying, the modified carbon fiber is obtained.
[0021] Preferably, the method for preparing the pretreated cerium oxide / reduced graphene oxide composite material comprises the following steps:
[0022] The cerium oxide / reduced graphene oxide composite material is added to anhydrous ethanol, and a silane coupling agent is added after ultrasonic dispersion for 30-60 minutes. The mixed solution is stirred at 60-70° C. for 6-10 hours, and the product is centrifugally washed and dried to obtain a pretreated cerium oxide / reduced graphene oxide composite material.
[0023] In summary, the present application includes at least one of the following beneficial technical effects:
[0024] 1. By adopting the above technical scheme, the present application adds rare earth element nano yttrium oxide to the iron-based alloy composite wear-resistant material for preparing roller sleeve cored wire. Nano yttrium oxide can refine the primary carbides of the alloy, improve the hardness and wear resistance of the surfacing layer, and can effectively improve the formability of the surfacing alloy; the addition of modified carbon fiber can change the microstructure of the surfacing alloy, so that the grains in the alloy are refined and the structure is homogenized. The refined grains can reduce the brittle tendency of the alloy and improve the toughness of the alloy. At the same time, it can further enhance the wear resistance of the iron-based alloy composite wear-resistant material and reduce the wear amount; by grafting and modifying the carbon fiber with cerium oxide / reduced graphene oxide composite materials, the tensile strength and modulus of the carbon fiber can be significantly enhanced, the wear resistance of the carbon fiber can be improved, the dispersion of the carbon fiber can be improved, and the carbon fiber can be avoided from agglomerating, thereby significantly improving the hardness, toughness and wear resistance of the roller sleeve cored wire.
[0025] 2. By adopting the above-mentioned technical scheme, the present application uses a silane coupling agent to modify the surface of carbon fiber and cerium oxide / reduced graphene oxide composite material, so that the surface of carbon fiber and cerium oxide / reduced graphene oxide composite material becomes more hydrophobic, effectively improving the dispersibility of the material, and improving the bonding ability of cerium oxide / reduced graphene oxide composite material with carbon fiber, thereby significantly enhancing the mechanical strength, wear resistance and dispersibility of carbon fiber. DETAILED DESCRIPTION
[0026] The present application is further described in detail below with reference to the embodiments.
[0027] The chemical reagents used in the preparation examples, embodiments and comparative examples provided by the present invention are all commercially available products, and their brands and manufacturers are as follows:
[0028] Carbon fiber, Beijing Mairida Technology Co., Ltd., OD: 150-200nm, Length: 10-30um;
[0029] Nano-yttrium oxide, Shanghai MacLean Biochemical Technology Co., Ltd., Y820611, 40 nm;
[0030] Reduced iron powder, Wuxi Minglu Pharmaceutical Technology Co., Ltd., 100 mesh;
[0031] High carbon ferrochrome, Guangdong Wengjiang Chemical Reagent Co., Ltd.
[0032] Preparation Example
[0033] Preparation Example 1
[0034] S1. 0.6 g of graphene oxide was added to 300 g of water, and ultrasonically dispersed at 22 kHz for 30 min. 4.2 g of cerium nitrate hexahydrate was added, and stirred for 3 h, and then allowed to stand for 24 h. The obtained mixture was transferred to a polytetrafluoroethylene-lined autoclave, and reacted at 160° C. for 12 h. After the reaction was completed, the mixture was cooled, washed with deionized water, and filtered until neutral. After freeze-drying for 6 h, a cerium oxide / reduced graphene oxide composite material was obtained;
[0035] S2. 1 g of the cerium oxide / reduced graphene oxide composite material prepared by S1 was added to 20 g of anhydrous ethanol, and after ultrasonic dispersion at 22 kHz for 30 min, a silane coupling agent KH-560 was added for 6 h, the mixed solution was stirred at 60 ° C for 6 h, the product was centrifugally washed with anhydrous ethanol, and dried to obtain a pretreated cerium oxide / reduced graphene oxide composite material;
[0036] S3. Add 0.1 g of carbon fiber to 40 g of anhydrous ethanol, ultrasonically disperse at 22 kHz for 1 h, then add 15 g of silane coupling agent KH-560, stir at 60 ° C for 6 h, then add 1 g of pretreated cerium oxide / reduced graphene oxide composite material prepared by S2, continue stirring for 6 h, wash with anhydrous ethanol and dry to obtain modified carbon fiber.
[0037] Preparation Example 2
[0038] S1. 0.9 g of graphene oxide was added to 450 g of water, and ultrasonically dispersed at 22.5 kHz for 45 min, and 6.3 g of cerium nitrate hexahydrate was added. After stirring for 4 h, the mixture was allowed to stand for 27 h. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and reacted at 180 ° C for 13.5 h. After the reaction was completed, the mixture was cooled, washed with deionized water, filtered to neutrality, and freeze-dried for 8 h to obtain a cerium oxide / reduced graphene oxide composite material;
[0039] S2. 3 g of the cerium oxide / reduced graphene oxide composite material prepared by S1 was added to 60 g of anhydrous ethanol, and 6 g of silane coupling agent KH-560 was added after ultrasonic dispersion at 22.5 kHz for 45 min. The mixed solution was stirred at 65 ° C for 8 h, and the product was centrifugally washed with anhydrous ethanol and dried to obtain a pretreated cerium oxide / reduced graphene oxide composite material;
[0040] S3. Add 0.2 g of carbon fiber to 60 g of anhydrous ethanol, add 15 g of silane coupling agent KH-560 after ultrasonic dispersion at 22.5 kHz for 1.5 h, stir at 65 ° C for 8 h, add 1 g of pretreated cerium oxide / reduced graphene oxide composite material prepared by S2, continue stirring for 8 h, wash with anhydrous ethanol and dry to obtain modified carbon fiber.
[0041] Preparation Example 3
[0042] S1. 1.2 g of graphene oxide was added to 600 g of water, and ultrasonically dispersed at 23 kHz for 60 min. 8.4 g of cerium nitrate hexahydrate was added, and stirred for 5 h, and then allowed to stand for 30 h. The obtained mixture was transferred to a polytetrafluoroethylene-lined autoclave, and reacted at 200 ° C for 15 h. After the reaction was completed, it was cooled, washed with deionized water, and filtered until neutral. After freeze-drying for 10 h, a cerium oxide / reduced graphene oxide composite material was obtained;
[0043] S2. 5 g of the cerium oxide / reduced graphene oxide composite material prepared by S1 was added to 100 g of anhydrous ethanol, and after ultrasonic dispersion at 23 kHz for 60 min, 6 g of silane coupling agent KH-560 was added, and the mixture was stirred at 70 ° C for 10 h, and the product was centrifugally washed with anhydrous ethanol and dried to obtain a pretreated cerium oxide / reduced graphene oxide composite material;
[0044] S3. Add 0.3 g of carbon fiber to 80 g of anhydrous ethanol, add 15 g of silane coupling agent KH-560 after ultrasonic dispersion at 23 kHz for 2 hours, stir at 70°C for 10 hours, add 1 g of pretreated cerium oxide / reduced graphene oxide composite material prepared by S2, continue stirring for 10 hours, wash with anhydrous ethanol and dry to obtain modified carbon fiber.
[0045] Preparation Example 4
[0046] The difference between Preparation Example 4 and Preparation Example 1 is that the mass of cerium nitrate hexahydrate used in S1 of Preparation Example 4 is 4.55 g.
[0047] Preparation Example 5
[0048] The difference between Preparation Example 5 and Preparation Example 1 is that the mass of cerium nitrate hexahydrate used in S1 of Preparation Example 5 is 4.8 g.
[0049] Preparation Example 6
[0050] The difference between Preparation Example 6 and Preparation Example 1 is that the mass of cerium nitrate hexahydrate used in S1 of Preparation Example 6 is 3.6 g.
[0051] Preparation Example 7
[0052] The difference between Preparation Example 7 and Preparation Example 1 is that the mass of cerium nitrate hexahydrate used in S1 of Preparation Example 7 is 5.4 g.
[0053] Preparation Example 8
[0054] The difference between Preparation Example 8 and Preparation Example 1 is that the mass of the silane coupling agent KH-560 used in S2 of Preparation Example 8 is 18 g.
[0055] Preparation Example 9
[0056] The difference between Preparation Example 9 and Preparation Example 1 is that the mass of the silane coupling agent KH-560 used in S2 of Preparation Example 9 is 30 g.
[0057] Preparation Example 10
[0058] The difference between Preparation Example 10 and Preparation Example 1 is that the mass of the silane coupling agent KH-560 used in S2 of Preparation Example 10 is 2 g.
[0059] Preparation Example 11
[0060] The difference between Preparation Example 11 and Preparation Example 1 is that the mass of the silane coupling agent KH-560 used in S2 of Preparation Example 11 is 36 g.
[0061] Preparation Example 12
[0062] The difference between Preparation Example 12 and Preparation Example 1 is that the mass of the silane coupling agent KH-560 used in S3 of Preparation Example 12 is 22.5 g.
[0063] Preparation Example 13
[0064] The difference between Preparation Example 13 and Preparation Example 1 is that the mass of the silane coupling agent KH-560 used in S3 of Preparation Example 13 is 30 g.
[0065] Preparation Example 14
[0066] The difference between Preparation Example 14 and Preparation Example 1 is that the mass of the silane coupling agent KH-560 used in S3 of Preparation Example 14 is 10 g.
[0067] Preparation Example 15
[0068] The difference between Preparation Example 15 and Preparation Example 1 is that the mass of the silane coupling agent KH-560 used in S3 of Preparation Example 15 is 35 g.
[0069] Preparation Example 16
[0070] The difference between Preparation Example 16 and Preparation Example 1 is that the mass of the pretreated cerium oxide / reduced graphene oxide composite material used in S3 of Preparation Example 16 is 2 g.
[0071] Preparation Example 17
[0072] The difference between Preparation Example 17 and Preparation Example 1 is that the mass of the pretreated cerium oxide / reduced graphene oxide composite material used in S3 of Preparation Example 17 is 3 g.
[0073] Preparation Example 18
[0074] The difference between Preparation Example 18 and Preparation Example 1 is that the mass of the pretreated cerium oxide / reduced graphene oxide composite material used in S3 of Preparation Example 18 is 0.5 g.
[0075] Preparation Example 19
[0076] The difference between Preparation Example 19 and Preparation Example 1 is that the mass of the pretreated cerium oxide / reduced graphene oxide composite material used in S3 of Preparation Example 19 is 4 g.
[0077] Example
[0078] Example 1
[0079] An iron-based alloy composite wear-resistant material for preparing roller sleeve cored wire is made of the following raw materials in percentage by mass: 52% high carbon ferrochrome, 3% chromium nitride, 1% graphite, 11% aluminum powder, 1.5% nano yttrium oxide, 1% modified carbon fiber, and 30.5% reduced iron powder;
[0080] The modified carbon fiber used in this example comes from Preparation Example 1.
[0081] Example 2
[0082] An iron-based alloy composite wear-resistant material for preparing roller sleeve core wire is made of the following raw materials in percentage by mass: 53% high-carbon ferrochrome, 2.5% chromium nitride, 1.3% graphite, 10% aluminum powder, 1.4% nano yttrium oxide, 1.3% modified carbon fiber, and 30.5% reduced iron powder;
[0083] The modified carbon fiber used in this example comes from Preparation Example 1.
[0084] Example 3
[0085] An iron-based alloy composite wear-resistant material for preparing roller sleeve core wire is made of the following raw materials in percentage by mass: 55% high-carbon ferrochrome, 2% chromium nitride, 1.5% graphite, 9.5% aluminum powder, 0.9% nano yttrium oxide, 1.7% modified carbon fiber, and 29.35% reduced iron powder;
[0086] The modified carbon fiber used in this example comes from Preparation Example 1.
[0087] Example 4
[0088] An iron-based alloy composite wear-resistant material for preparing roller sleeve core wire is made of the following raw materials in percentage by mass: 57% high-carbon ferrochrome, 1.5% chromium nitride, 1.7% graphite, 9% aluminum powder, 1.4% nano yttrium oxide, 1.7% modified carbon fiber, and 29.4% reduced iron powder;
[0089] The modified carbon fiber used in this example comes from Preparation Example 1.
[0090] Example 5
[0091] An iron-based alloy composite wear-resistant material for preparing roller sleeve core wire is made of the following raw materials in percentage by mass: 58% high-carbon ferrochrome, 1% chromium nitride, 2% graphite, 8% aluminum powder, 0.8% nano yttrium oxide, 2% modified carbon fiber, and 28.2% reduced iron powder;
[0092] The modified carbon fiber used in this example comes from Preparation Example 1.
[0093] Example 6
[0094] The difference between Example 6 and Example 1 is that the modified carbon fiber used in Example 6 comes from Preparation Example 2.
[0095] Example 7
[0096] The difference between Example 7 and Example 1 is that the modified carbon fiber used in Example 7 comes from Preparation Example 3.
[0097] Example 8
[0098] The difference between Example 8 and Example 1 is that the modified carbon fiber used in Example 8 comes from Preparation Example 4.
[0099] Example 9
[0100] The difference between Example 9 and Example 1 is that the modified carbon fiber used in Example 9 comes from Preparation Example 5.
[0101] Example 10
[0102] The difference between Example 10 and Example 1 is that the modified carbon fiber used in Example 10 comes from Preparation Example 6.
[0103] Embodiment 11
[0104] The difference between Example 11 and Example 1 is that the modified carbon fiber used in Example 11 comes from Preparation Example 7.
[0105] Example 12
[0106] The difference between Example 12 and Example 1 is that the modified carbon fiber used in Example 12 comes from Preparation Example 8.
[0107] Example 13
[0108] The difference between Example 13 and Example 1 is that the modified carbon fiber used in Example 13 comes from Preparation Example 9.
[0109] Embodiment 14
[0110] The difference between Example 14 and Example 1 is that the modified carbon fiber used in Example 14 comes from Preparation Example 10.
[0111] Embodiment 15
[0112] The difference between Example 15 and Example 1 is that the modified carbon fiber used in Example 15 comes from Preparation Example 11.
[0113] Example 16
[0114] The difference between Example 16 and Example 1 is that the modified carbon fiber used in Example 16 comes from Preparation Example 12.
[0115] Embodiment 17
[0116] The difference between Example 17 and Example 1 is that the modified carbon fiber used in Example 17 comes from Preparation Example 13.
[0117] Embodiment 18
[0118] The difference between Example 18 and Example 1 is that the modified carbon fiber used in Example 18 comes from Preparation Example 14.
[0119] Embodiment 19
[0120] The difference between Example 19 and Example 1 is that the modified carbon fiber used in Example 19 comes from Preparation Example 15.
[0121] Embodiment 20
[0122] The difference between Example 20 and Example 1 is that the modified carbon fiber used in Example 20 comes from Preparation Example 16.
[0123] Embodiment 21
[0124] The difference between Example 21 and Example 1 is that the modified carbon fiber used in Example 21 comes from Preparation Example 17.
[0125] Embodiment 22
[0126] The difference between Example 22 and Example 1 is that the modified carbon fiber used in Example 22 comes from Preparation Example 18.
[0127] Embodiment 23
[0128] The difference between Example 23 and Example 1 is that the modified carbon fiber used in Example 23 comes from Preparation Example 19.
[0129] Comparative Example
[0130] Comparative Example 1
[0131] The difference between Comparative Example 1 and Example 1 is that nano yttrium oxide is not added in Comparative Example 1; An iron-based alloy composite wear-resistant material for preparing a roller sleeve core wire is made of the following raw materials in percentage by mass: 52% high carbon ferrochrome, 3% chromium nitride, 1% graphite, 11% aluminum powder, 1% modified carbon fiber, and 32% reduced iron powder;
[0132] The modified carbon fiber used in this comparative example comes from Preparation Example 1.
[0133] Comparative Example 2
[0134] The difference between Comparative Example 2 and Example 1 is that the content of nano yttrium oxide added in Comparative Example 2 is 4%; an iron-based alloy composite wear-resistant material for preparing roller sleeve core wire is made of the following raw materials in percentage by mass: 52% high carbon ferrochrome, 3% chromium nitride, 1% graphite, 11% aluminum powder, 4% nano yttrium oxide, 1% modified carbon fiber, and 28% reduced iron powder;
[0135] The modified carbon fiber used in this comparative example comes from Preparation Example 1.
[0136] Comparative Example 3
[0137] The difference between Comparative Example 3 and Example 1 is that no modified carbon fiber is added in Comparative Example 3; an iron-based alloy composite wear-resistant material for preparing roller sleeve core wire is made of the following raw materials in percentage by mass: 52% high carbon ferrochrome, 3% chromium nitride, 1% graphite, 11% aluminum powder, 1.5% nano yttrium oxide, and 31.5% reduced iron powder.
[0138] Comparative Example 4
[0139] The difference between Comparative Example 4 and Example 1 is that the addition amount of modified carbon fiber in Comparative Example 4 is 5%; an iron-based alloy composite wear-resistant material for preparing roller sleeve core wire is made of the following raw materials in percentage by mass: 52% high carbon ferrochrome, 3% chromium nitride, 1% graphite, 11% aluminum powder, 1.5% nano yttrium oxide, and 26.5% reduced iron powder;
[0140] The modified carbon fiber used in this comparative example comes from Preparation Example 1.
[0141] Performance testing
[0142] The iron-based alloy composite wear-resistant material for preparing the roller sleeve flux-cored wire obtained in Examples 1-23 and Comparative Examples 1-4 was filtered through a 60-mesh screen to remove large particles of powder and impurities; the filtered powder was placed in a welding rod drying furnace to dry and remove the moisture therein, and then the filtered powder was placed in a planetary ball mill and operated at a speed of 250 rpm for 5 minutes to stir the powder evenly. Then the powder was prepared and formed in a YHZ-1 flux-cored welding wire forming machine manufactured by Tianjin Sanying Welding Co., Ltd., and the formed flux-cored welding wire was reduced in diameter by four groups of reducing and drawing machines, and the diameter of the welding wire was reduced from Φ4.0 mm to Φ3.2 mm, Φ2.7 mm, and Φ2.4 mm in sequence.
[0143] The open arc surfacing experiment was carried out on the Q235 substrate using an MZC-1250 automatic submerged arc welding machine. The surfacing alloy was prepared by a 2-layer 4-pass surfacing method. The wire dry extension was controlled to be 35 mm, the welding speed was 20 mm / min, and the interlayer temperature was 200 °C. The obtained surfacing alloy was subjected to hardness test and abrasive wear test.
[0144] (1) Hardness test
[0145] The hardness of the cladding alloy was measured using a HRC-150 Rockwell hardness tester. In order to ensure the accuracy of the hardness value of the cladding alloy, five-point measurements were taken, and the average value of the five measurements was finally used as the hardness value of the cladding alloy. The test parameters were: load 150kg, loading time 15s, and the results are shown in Table 1.
[0146] (2) Abrasive wear test
[0147] The surface of the weld overlay was processed to be smooth by a grinder to prevent the uneven surface of the wear specimen from affecting the experimental results. The treated weld overlay was cut by an electric spark wire cutting machine, and the specimen size was 56×27×11mm. The MLS-23 rubber wheel wet sand wear tester was used for abrasive wear test. Before the abrasive wear test, the specimen was ultrasonically cleaned and dried. The mass M of the specimen before wear was weighed with an electronic balance with an accuracy of 0.001g. 0Then the sample was loaded into the abrasive wear tester and a mixture of water and quartz sand was added to conduct an abrasive wear test. The experimental parameters were: the rubber wheel speed was 240 rpm, the wear time was 3 min, and the maximum positive pressure of the rubber wheel was 23 kg. After the wear test, the mortar on the surface of the sample was cleaned and dried, and then the mass M after wear was weighed with a balance. 1 , then the wear weight loss ΔM can be obtained, and its expression is as follows:
[0148] ΔM=M 1 -M 0
[0149] The results are shown in Table 1.
[0150] The specific test results are as follows:
[0151] Table 1 Performance test results
[0152]
[0153]
[0154] It can be seen from the inspection results of Table 1 that the iron-based alloy composite wear-resistant material for the preparation of roller sleeve flux-cored wire provided in the present application can effectively improve the hardness of the surfacing alloy and effectively reduce the wear of the surfacing alloy, indicating that the iron-based alloy composite wear-resistant material for the preparation of roller sleeve flux-cored wire provided in the present application has excellent mechanical strength, toughness and wear resistance.
[0155] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An iron-based alloy composite wear-resistant material for preparing roller sleeve cored wire, characterized in that: The raw materials include 52-58% high carbon ferrochrome, 1-3% chromium nitride, 1-2% graphite, 8-11% aluminum powder, 0.8-1.5% nano yttrium oxide, 1-2% modified carbon fiber, and the balance is reduced iron powder by mass percentage; the modified carbon fiber is cerium oxide / reduced graphene oxide composite material modified carbon fiber.
2. The iron-based alloy composite wear-resistant material for preparing roller sleeve cored wire according to claim 1, characterized in that: The raw materials include 53-57% high carbon ferrochrome, 1.5-2.5% chromium nitride, 1.3-1.7% graphite, 9-10% aluminum powder, 0.9-1.4% nano yttrium oxide, 1.3-1.7% modified carbon fiber, and the balance is reduced iron powder.
3. The iron-based alloy composite wear-resistant material for preparing roller sleeve cored wire according to claim 1, characterized in that: The raw materials include 55% high carbon ferrochrome, 2% chromium nitride, 1.5% graphite, 9.5% aluminum powder, 1.15% nano yttrium oxide, 1.5% modified carbon fiber, and the remainder is reduced iron powder.
4. The iron-based alloy composite wear-resistant material for preparing roller sleeve cored wire according to claim 1, 2 or 3, characterized in that: The modified carbon fiber is prepared from the following raw materials in parts by weight: 0.1-0.3 parts of carbon fiber, 1-3 parts of pretreated cerium oxide / reduced graphene oxide composite material, 40-80 parts of anhydrous ethanol, and 15-30 parts of a silane coupling agent.
5. The iron-based alloy composite wear-resistant material for preparing roller sleeve cored wire according to claim 4, characterized in that: The pretreated cerium oxide / reduced graphene oxide composite material is prepared from the following raw materials in parts by weight: 1-5 parts of cerium oxide / reduced graphene oxide composite material, 20-100 parts of anhydrous ethanol, and 6-30 parts of a silane coupling agent.
6. The iron-based alloy composite wear-resistant material for preparing roller sleeve cored wire according to claim 5, characterized in that: The cerium oxide / reduced graphene oxide composite material is prepared from the following raw materials in parts by weight: 0.6-1.2 parts of graphene oxide, 300-600 parts of water, and 4.2-9.6 parts of cerium nitrate hexahydrate.
7. The iron-based alloy composite wear-resistant material for preparing roller sleeve cored wire according to claim 6, characterized in that: The mass ratio of the graphene oxide to the cerium nitrate hexahydrate is 1:7-8.
8. The iron-based alloy composite wear-resistant material for preparing roller sleeve cored wire according to claim 6, characterized in that: The preparation method of the cerium oxide / reduced graphene oxide composite material comprises the following steps: Graphene oxide is added to water, ultrasonically dispersed, cerium nitrate hexahydrate is added, stirred for 3-5 hours, and allowed to stand for 24-30 hours. The obtained mixture is transferred to a polytetrafluoroethylene-lined high-pressure reactor and reacted at 160-200°C for 12-15 hours. After the reaction is completed, it is cooled, washed with deionized water, filtered to neutrality, and freeze-dried for 6-10 hours to obtain a cerium oxide / reduced graphene oxide composite material.
9. The iron-based alloy composite wear-resistant material for preparing roller sleeve cored wire according to claim 4, characterized in that: The method for preparing the modified carbon fiber comprises the following steps: The carbon fiber is added to anhydrous ethanol, ultrasonically dispersed for 1-2 hours, and then a silane coupling agent is added, stirred at 60-70° C. for 6-10 hours, and then the pretreated cerium oxide / reduced graphene oxide composite material is added, and stirring is continued for 6-10 hours. After washing and drying, the modified carbon fiber is obtained.
10. The iron-based alloy composite wear-resistant material for preparing roller sleeve cored wire according to claim 5, characterized in that: The method for preparing the pretreated cerium oxide / reduced graphene oxide composite material comprises the following steps: The cerium oxide / reduced graphene oxide composite material is added to anhydrous ethanol, and a silane coupling agent is added after ultrasonic dispersion for 30-60 minutes. The mixed solution is stirred at 60-70° C. for 6-10 hours, and the product is centrifugally washed and dried to obtain a pretreated cerium oxide / reduced graphene oxide composite material.
Citation Information
Patent Citations
Welding wire for repairing worn positions of wear-resistant components and manufacturing method thereof
CN103418941A
Iron-based self-protection flux-cored wire, surfacing alloy manufactured with iron-based self-protection flux-cored wire and method for manufacturing iron-based self-protection flux-cored wire
CN104708234A
High-efficient energy-saving and surfacing layer well-forming self-shielded flux-cored welding wire and manufacture method thereof
CN106041356A
Build-up welding material for membrane water-cooling wall and repair welding method
CN109848605A
Wear-resistant and crack-resistant welding wire for surfacing and preparation method thereof
CN115476071A